2008
DOI: 10.1016/j.jana.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Love and Hope: Caregiving for Thai Children With HIV Infection

Abstract: In this grounded theory study, the author explored how primary caregivers dealt with problems in caring for children with HIV infection in Thailand. A total of 27 family caregivers of HIV-infected children participated in open-ended interviews. Maintaining love and hope represented a condition for the continuing process of caregiving. Caregivers had to deal with the stigma of AIDS while providing care for children with HIV. They had high anxiety and fear of loss, bore much burden of care, and faced many diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The influencing factors such as their child's health, knowledge, and experience, connecting with others, being in the loop, and reaffirming faith also influenced parents' need for hope and caused them to lose sight of their hope. Previous research have described similar aspects of hope including fading hope, 28 dislodging of hopefulness, 17 threatened hope, 23 and endangered hope. 9 Realizing the need for hope was an important strategy used in restructuring hope.…”
Section: Summary Of the Model: Keeping Hope Possiblementioning
confidence: 86%
“…The influencing factors such as their child's health, knowledge, and experience, connecting with others, being in the loop, and reaffirming faith also influenced parents' need for hope and caused them to lose sight of their hope. Previous research have described similar aspects of hope including fading hope, 28 dislodging of hopefulness, 17 threatened hope, 23 and endangered hope. 9 Realizing the need for hope was an important strategy used in restructuring hope.…”
Section: Summary Of the Model: Keeping Hope Possiblementioning
confidence: 86%
“…Similar results have been shown in previous studies. In these studies, family members and sometimes the caregivers themselves were infected with HIV, which might magnify the psychological problems among caregivers, as they would struggle with ongoing HIV infection and face more difficulties related to HIV specific medical demands and problems such as cost of treatment and service shortfalls (Kipp et al, 2007; Meadows, Le Maréchal, & Catalán, 1999; Thampanichawat, 2008; Wiener et al, 2001; Wight, 2000). The strong association between family SES and depression found in this study were consistent with the results of previous studies reporting that many households affected with HIV were experiencing significant financial hardship which might be an important contributor to caregiver anxiety and depression (Flaskerud & Tabora, 1998; Ji at al., 2007; Linsk & Mason, 2004; Songwathana, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to caring for OVC, there are multiple routes through which caregivers can be affected by HIV/AIDS. These additional routes include economic burdens of child-rearing, physical and health impacts related to caregiving, and emotional impacts related to the strain of living with or caring for persons living with HIV/AIDS (PLWHA) (Freeman & Nkomo, 2006; Ji, Li, Lin, & Sun, 2007; Joslin & Harrison, 2002; Linsk & Mason, 2004; Paige & Johnson, 1997; Safman, 2004; Thampanichawat, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Although hope research in nursing has received a great deal of attention since the 1980s, the hope of informal caregivers including spouses, offspring, relatives, and parents who have children with LLIs and LTIs, such as cancer (Eapen & Revesz, 2003; Kylma & Juvakka, 2007), HIV/AIDS (Thampanichawat, 2008), and spina bifida (Kirpalani et al., 2000), have been studied to a lesser degree. Researchers have suggested that parents of children with LLIs and LTIs experienced distress, stress, anxiety, and altered coping (McGrath, 2001; Pai et al., 2007) that affected their overall health and caregiving abilities (Kars, Duijnstee, Pool, van Delden, & Grypdonck, 2008; Svavarsdottir, 2005).…”
Section: Paradigms and Parental Hopementioning
confidence: 99%
“…Researchers have suggested that parents of children with LLIs and LTIs experienced distress, stress, anxiety, and altered coping (McGrath, 2001; Pai et al., 2007) that affected their overall health and caregiving abilities (Kars, Duijnstee, Pool, van Delden, & Grypdonck, 2008; Svavarsdottir, 2005). These parents faced overwhelming difficulties, but out of their dilemma emerged hope, which for them was a helpful resource (Kauser, Jevne, & Sobsey, 2003), a survival tool (Reder & Serwint, 2009), and was used to continue caregiving (Kirpalani et al., 2000; Samson et al., 2009; Thampanichawat, 2008). Because parents identified hope as being important, gaining a clear understanding of parental hope in the context of caring for a child with an LLI or LTI is imperative.…”
Section: Paradigms and Parental Hopementioning
confidence: 99%